The effects of particle precipitation on the ionosphere in the South Atlantic Anomaly Region - Haggard, Raymond (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1994)
The first ground based observations of aeronomic phenomena in the South Atlantic Anomaly Region are presented. These data show that enhancements in foF2 and foE can be directly attributed to precipitated electron energy fluxes in the Anomaly Region. The regular occurrence of particle induced sporadic-E ionization is also presented together with the first measurable 391.4 nm airglow radiation of about 16 R. The first comprehensive survey of energy fluxes carried by energetic particles using satellites is also presented for both daytime and nighttime as well as the seasonal fluctuations. We found that the nocturnally precipitated electron energy fluxes varied between 1 x 10â »â ´ and 38 x 10â »â ´ erg cmÂ²sâ »Â¹, depending upon magnetic activity and season, whereas the daytime precipitated electron energy fluxes tended to vary between 1 x 10â »Â³ and 8 x 10â »Â³ erg cmâ »Â²sâ »Â¹, with a tendency to decrease during magnetically active periods. Electron density and temperature contours as well as NOâ º and 0â º ions contours for nighttime are also presented. The main conclusion of the study is that precipitating electrons provide a significant and sometimes dominant source of ionization in the ionosphere over the South Atlantic Anomaly Region.
Keywords: Precipitation (Chemistry); Ionosphere; Ionospheric electron density